Recent advances in hydrogels for treating periodontal diseases and oral mucosal diseases - Gui, Yu; Zhang, Yunpeng; Xu, Haoyang; Yang, Wanli; Huang, Haitong; Gu, Mengqin; Sun, Yu (Frontiers in Bioengineering and Biotechnology, 2025)
Periodontal and oral mucosal diseases are prevalent oral health challenges. Thanks to the natural constraints imposed by the moist and complex intraoral environment, current therapeutic modalities are significantly limited by two key issues: inefficient, low sustained drug release and short intraoral drug retention times, both of which compromise therapeutic efficacy. To address these challenges, hydrogels—a novel class of biomaterials with unique biological and physicochemical properties—have emerged as promising solutions. Hydrogels, with their 3-dimensional (3D) polymer network, are promising biological reagents, particularly for drug delivery. They achieve controlled and sustained release at target sites, and coupled to their therapeutic outcomes, their use in oral healthcare is critical. Consequently, hydrogels have been extensively investigated in both foundational and clinical research, particularly within a wound dressing context. This article systematically examines the limitations associated with conventional therapies and elucidates the mechanisms underpinning the therapeutic efficacy of hydrogels in managing different periodontal and oral mucosal diseases. Furthermore, we explore the clinical challenges and opportunities associated with applying hydrogel-based strategies in oral therapeutics, and we propose future directions for hydrogel research and development.